Evaluation of three antigens by enzyme-linked immunosorbent assay (ELISA) for the detection of Mycobacterium bovis infection in Indian cattle for field use - Maheshwari, Arpan; Verma, Rishendra (The Indian Journal of Animal Sciences, 2005)
Crude antigens.viz. purified protein derivative (PPD) and protein rich soluble extract and a species-specific phenolic glycolipid of mycobacterium bovis AN5 origin were used as antigens. Group A cattle herd consisted of animals not tested with tuberculin for last 12 years and no record of tuberculosis in these animals was available. Group B belonged to cattle, which are not tuberculin tested within previous 60 days and group C included cattle which had tuberculin testing previously at least 14 days earlier. In all 241 sera were collected for the measurement of lgG by ELISA assays by 3 antigens. Considerly 2 ways of determination of the cut-off values. viz. mean ±2 SD or histogram, we used the histogram cut-off value for the ELISA assay with PPD showed 39%, 72% sensitivity and 90% specificity in groups B and C, respectively. with protein rich soluble extract antigen, ELISA showed 36%. 73% sensitivity and 85% specificity in groups B and C, respectively, with PGL showed 79%, 67% sensitivity and 92% specificity in groups B and C respectively. These findings indicated that the sensitivity and specificity of the assay depends on the population tested. our study suggested that protein rich soluble extract and PGL (deacylated) antigens may be used simultaneously to screen animals so that cattle is not missed from detection if species-specific anti-PGL antibodies were absent. The role of cut-off value has been discussed.